Prinsip – Prinsip Montessori dalam Membentuk Kemandirian pada Anak Usia Dini di Paud Junior SKB Ungaran - Adetirta Ayomi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to describe the application of Montessori principles in shaping early childhood independence at PAUD Junior SKB Ungaran. Using a descriptive qualitative approach, the research subjects included principals, teachers, students, and parents. The research was conducted in May-June 2025 with data collection techniques in the form of observation, in-depth interviews, and documentation. Data validity was ensured through source triangulation, and data analysis was conducted using the Miles and Huberman model. The results show that Montessori principles such as a prepared environment, freedom of choice, concrete activities, and the role of the teacher as a facilitator have been consistently applied. Children appear independent in taking care of themselves, choosing activities, completing tasks, and tidying up tools. Cross-age classes also support social development and responsibility. In conclusion, consistent application of Montessori principles supported by a conducive environment significantly contributes to early childhood independence.